(untitled) (Transport systems and technologies, 2021)
With the development and distribution of embedded control systems for industrial and household equipment, the generation of speed trajectories for systems controlled by motors, other rotary mechanisms and units remains an urgent task. Adjusting the acceleration profile improves the quality of the system, and the use of adaptive design of automatic controls theoretically increases the speed of work. Implementation of compulsory software control of the speed profile or its automatic generation, according to the current parameters of the system, reduces the risks associated with the human factor and protects the system from operator inaccuracy. Reducing the factor of undesirable interference and creating a model of controlled environment increases the level of production safety, therefore, improving and modernizing the existing approach to managing high-speed industrial systems is a necessary condition for its further development. This article proposes to consider an improved model of a software speed controller that controls the pulse driver of a stepper motor. Based on existing research and corporate solutions during production development used experimentally the adaptive design of the state machine of the system, makes it possible to vary the speed of rotation of the stepper motor during the operation of the system in real time.